Educação infantil entre narrativas e poemas: a literatura como espaço de fruição e de constituição da linguagem oral e escrita - Vasconcelos, Daniella Borges de Faria (2024)
This dissertation explores the use of literary narratives as a methodological resource for developing the oral and written language of children aged 4 to 5 in a Municipal Early Childhood Education Center (CMEI) in Goiânia, Goiás. The guiding research question is: How can literary narratives, poems, and songs contribute to literary literacy and language development in Early Childhood Education? Based on this question, the general objective of the dissertation is to investigate how narratives, together with poems, can support the literary literacy of children and foster an interest in reading in the EI-D1 group (3 years old) of a CMEI in Goiânia. The study is grounded in a pedagogical approach that uses literary narratives as a tool for language development. The methodology adopted was action research, involving the continuous implementation and evaluation of pedagogical practices through an action plan that included diversifying learning spaces and storytelling activities. The dissertation is structured to address the contribution of literary reading to the formation of oral and written language in early childhood education. The study also draws on theories about the importance of exposing children to different forms of literary art from early childhood, highlighting how such experiences help build a rich and diverse cultural repertoire. The first chapter discusses the contribution of literary reading to the development of oral and written language in children, exploring the benefits of reading for oral expression and the challenges of learning to write. It emphasizes the role of literary texts and the importance of an affective approach in the interaction between the child, the family, and the text. The second chapter examines the aesthetic education of children through narrative and poetry, focusing on storytelling. The third chapter presents the reading corpus used in the research. The fourth chapter details the action research conducted in a CMEI in Goiânia, which investigated the impact of playful and creative strategies in promoting literary literacy. The research findings underscore the importance of reading in Early Childhood Education, highlighting diverse pedagogical practices that stimulate creativity and strengthen emotional bonds between children and families. The dissertation’s educational product is an e-book, HISTÓRIA DE PASSARINHO: Narratives Inspired by the Flights and Soarings of Childhood and Children, which documents the development of the reading project, including records of activities and reflections. The aim is to inspire similar initiatives and contribute to the promotion of literary literacy in early childhood education. Both the product and the dissertation were developed during the Professional Master’s Program in Teaching in Basic Education, part of the Stricto Sensu Graduate Program of CEPAE/UFG. The conclusion confirms that diversifying learning spaces and incorporating storytelling have a significant positive impact on children’s development, fostering creativity, motor coordination, empathy, and active participation, as well as strengthening their emotional connection with the school—ultimately contributing to a more engaging and holistic learning experience